Gambaran kecenderungan depresi pada remaja - Wahyuni, Fitri; Astuti, Yuni (Holistik Jurnal Kesehatan, 2025)
Background: Adolescence is a developmental transition phase from childhood to adulthood, characterized by significant physical, psychological, social, and emotional changes. During this period, adolescents face complex academic, social, and environmental demands, requiring a high level of adaptation. These pressures can contribute to vulnerability to mental health disorders, particularly depression. Depression in adolescents can seriously impact emotional well-being, social relationships, and academic achievement, and can increase the risk of suicide. Purpose: To determine the prevalence of depression in adolescents. Method: This was a descriptive study with a cross-sectional design, conducted from July to August 2025. The sample was selected using total sampling based on inclusion and exclusion criteria. A total of 620 respondents were recruited. Data collection used the Children's Depression Inventory (CDI) questionnaire. Results: The average age of respondents was 13,329 years with a standard deviation of 0.748, ranging from 11 to 15 years. The majority of respondents (360) were female (58.1%). Most children were the eldest in the family (247 children) (39.8%). Furthermore, most respondents had siblings (560 children) (90.3%). Most respondents' parents worked as private sector employees (380 children) (61.3%). Most respondents lived with their parents (389 children) (62.7%). Most parents were not divorced (530 children) (85.5%). Most respondents had experienced the loss of a parent or relative (441 children) (71.1%). Based on data on depression trends, it appears that most respondents (620 children) had experienced it (45.8%). Conclusion: The prevalence of depression in adolescents was recorded at 620 (45.8%), with a mean age of 13 years (50.6%), and a female gender predominance (58.1%). The highest mean domain was negative mood.    Keywords: Adolescents; Depression; Mental Health.  Pendahuluan: Masa remaja merupakan fase perkembangan transisi dari anak-anak menuju dewasa yang ditandai oleh perubahan besar dalam aspek fisik, psikologis, sosial, dan emosional. Pada masa ini, remaja menghadapi berbagai tuntutan akademik, sosial, dan lingkungan yang kompleks, sehingga memerlukan kemampuan adaptasi yang tinggi. Tekanan tersebut dapat menimbulkan kerentanan terhadap gangguan kesehatan mental, terutama depresi. Depresi pada remaja dapat berdampak serius terhadap kesejahteraan emosional, hubungan sosial, serta prestasi dan berisiko melakukan bunuh diri. Tujuan: Untuk mengetahui gambaran kecenderungan depresi pada  remaja. Metode: Jenis penelitian deskriptif dengan desain cross sectional, dilakukan pada Juli-Agustus 2025. Pemilihan sampel menggunakan total sampling berdasarkan kriteria inklusi dan eksklusi. Jumlah sampel sebanyak 620 responden. Pengumpulan data menggunakan kuesioner Children’s Depression Inventory (CDI). Hasil: Usia rata-rata responden 13.329 tahun dengan standar deviasi 0.748 pada rentang 11-15 tahun. Mayoitas responden berjenis kelamin perempuan 360 (58.1%). Kebanyakan anak adalah anak pertama dalam keluarganya, yaitu 247 (39.8%), Selain itu, sebagian besar responden memiliki saudara, yaitu sebesar 560 (90.3%). Mayoritas pekerjaan oran tua responden sebagai karyawan swasta, yaitu sebanyak 380 (61.3%). Kebanyakan responden tinggal bersama orang tuanya, yaitu sebanyak 389 (62.7%). Kebanyakan orang tua tidak bercerai, yaitu sebesar 530 (85.5%). Sebagian besar responden pernah mengalami kehilangan orang tua atau kerabat, yaitu sebesar 441 (71.1%). Berdasarkan data kecenderungan depresi, ternyata sebagian besar responden hampir mengalaminya yaitu sebanyak 620 (45.8%). Simpulan: Kecenderungan depresi pada remaja tercatat sejumlah 620 (45.8%) dengan usia rata-rata 13 tahun (50.6%) dan didominasi jenis kelamin perempuan (58.1%). Domain rata-rata tertinggi pada domain negative mood (suasana hati negatif).   Kata Kunci: Depresi; Kesehatan Mental; Remaja.